ANTENA SUSUN 4×1 MIKROSTRIP MENGGUNAKAN BIQUAD PATCH PADA FREKUENSI X-BAND UNTUK TELEKOMUNIKASI TERESTRIAL - Hidayat, M. Reza; Kurniawan, Muhammad Luthfi (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2022)
The need for information exchange that encourages the development of telecommunications technology that can be a medium for delivering information to connect various places on the earth's surface or called terrestrial telecommunications. In wireless communication, the use of radio waves as a medium for propagation of information is considered more effective than physical media such as cables. A high radio frequency value such as X-Band will result in a smaller dimensional device. The use of microstrip type antennas has advantages in terms of small dimensions, inexpensive fabrication, and simple design but has low gain. Therefore, the design of a microstrip antenna with the array method becomes a solution that can be used in applications in terrestrial telecommunications. In this research, a microstrip antenna with a biquad-shaped patch has been designed and realized with a 4×1 array method that operates in the X-Band frequency band. This antenna works at a frequency of 11.96 GHz with a return loss of -23.51 dB and a VSWR of 1.13.